2022
DOI: 10.3389/fpsyg.2021.762994
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Employees’ Perceived Intrinsic Motivation on Knowledge Sharing and Creative Self-Efficacy

Abstract: Knowledge sharing is the major driving force to maintain enterprises’ competitiveness. This study extends the current knowledge-sharing research by considering knowledge sharing as comprising four types: automatic response, rational reflection, ridiculed reflection, and deprived reflection, based on Kahneman’s (2011) types of system thinking. Drawing on the motivation-action-outcome model, this study explored how individuals’ intrinsic motivation can guide the action of knowledge sharing and reflect the outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In the research of Yang and Cheng (2009), it is emphasized that the KSB exhibited in the field of information technology has a positive impact on creative self-efficacy. In their study, (Parhamnia, Farahian and Rajabi, 2022;Sun, Hong and Ye, 2022) found that KSB had a positive impact on CSE. Considering this knowledge, it is possible to make the assumption that workers will improve their CSE as a result of the new knowledge they learn…”
Section: Knowledge Sharing Behavior and Creative Self-efficacymentioning
confidence: 95%
“…In the research of Yang and Cheng (2009), it is emphasized that the KSB exhibited in the field of information technology has a positive impact on creative self-efficacy. In their study, (Parhamnia, Farahian and Rajabi, 2022;Sun, Hong and Ye, 2022) found that KSB had a positive impact on CSE. Considering this knowledge, it is possible to make the assumption that workers will improve their CSE as a result of the new knowledge they learn…”
Section: Knowledge Sharing Behavior and Creative Self-efficacymentioning
confidence: 95%
“…Intrinsic motivation can be further divided in four subdimensions, i.e., enjoyment of an activity, perceived competence in such activity, importance given to the activity, and pressure felt while carrying out the activity [4]. This variable with its subdimensions has been the center of interest of research in a variety of fields, and several instruments were built for its assessment [5][6][7]. A tool standing out in this sense is the Intrinsic Motivation Inventory (IMI) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, ES-e can be influenced by environmental knowledge and environmental affect. Previous studies showed that rational reflection as an indicator of knowledge sharing was positively associated with creative self-efficacy (Sun et al, 2021).…”
mentioning
confidence: 97%